John Maxwell Coetzee’s Disgrace: A Work of Racial Complexity - Subedi, Narendra Raj (Interdisciplinary Journal of Management and Social Sciences, 2021)
Since Literary work is a creative work which is not limited by time and place. In this regard, John Maxwell Coetzee’s novel Disgrace (1999) is no exception. Written in South Africa during the postcolonial era but still it reflects racial segregation. The story in the novel from Prof. David Lurie’s point of view. The events and its main characters are described and examined from the perspective of a white Settler in South Africa. David’s partial vision towards the black makes us realize that there is a kind of racial complexity. The author of this article aims to examine the key issues related to racial and social injustice. Racism is a man-made phenomenon as Huton Calvin writes, ". . . learned behaviour and learned emotions on the part of people towards another group; whose physical characteristics are dissimilar to the former group . . . as if doesn’t belong to the human race" (Calvin, 175). The characters in Disgrace are also in two category: White and non-white where David represents the first and Petrus, Melanie and many other fall under the second category. The gap between the two has got a problem, even after the colonial Africa. This problem should be addressed examining through the racial complexity that exists the post apartheid era in South Africa.